Structural, magnetic and optical properties of a dilute magnetic semiconductor based on Ce1−xCoxO2 thin film grown on LaAlO3. (December 2015) - Mahmoud, Waleed E.; Al-Ghamdi, A.A.; Al-Agel, F.A.; Al-Arfaj, E.; Shokr, F.S.; Al-Gahtany, S.A.; Alshahrie, Ahmed; Jalled, Ouissem; Bronstein, L.M.; Beall, Gary W.
Graphical abstract: Highlights: Co doped CeO2 was grown on LaAlO3 (0 0 1) via a modified sol–gel spin-coating technique. The concentration of the Co ions was varied from 1 to 15 at.%. The incorporation of 5 at.% of Mn ions was found to provide formation of exceptionally magnetic moment. This amount demonstrated a giant magnetic moment of 1.09 μB /Co. This amount reduced the optical band gap and enhanced the optical performance. Abstract: The enhancement of the room temperature ferromagnetism and optical properties of the dilute magnetic metal oxides is a crucial clue to construct spin-based optoelectronic devices. In this work, Ce1− x Co x O2 (0.01 ≤  x  ≤0.15) thin films were prepared via ethylene glycol modified sol–gel spin coating technique on the LaAlO3 (0 0 1) substrate to enhance their room temperature ferromagnetism and optical properties. The structures, magnetic and optical properties of the prepared films were characterized by X-ray diffraction, atomic force microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, SQUID magnetometer, X-ray photoelectron spectroscopy and UV–vis spectrophotometer. The results demonstrated that a single phase cubic structure was formed, implying the substitution of Co ions into the Ce ions sites. The prepared films showed room temperature ferromagnetism with saturation magnetic moment of 1.09 μB /Co was achieved for 5 at.% Co-doped CeO2 . This film exhibited high optical transparency of 85% and low optical band energy gap of 3.39 eV. The improved magnetic and optical properties are argued to the increase of the density of the oxygen vacancies into the cerium oxide crystal structure due to the incorporation of Co ions.